Confidence Matters: Self-efficacy Moderates the Credit that Supervisors Give to Adaptive and Proactive Role Behaviours - Nguyen, H.; Johnson, A.; Collins, C.; Parker, Sharon (Wiley-Blackwell Publishing Ltd., 2017)
In complex and uncertain work environments, employees need to not only be proficient in carrying out their core duties, but also to be adaptive (able to cope and respond to unpredictable events) and proactive (able to anticipate the situation and act in a self-directed way) in their work roles. In this study we investigate the extent to which supervisors actually give credit to adaptive and proactive role behaviours when they judge employees’ overall job performance. Drawing on attribution theory, we propose that the extent to which these role behaviours are valued by supervisors will be enhanced by employees’ confidence for relevant role behaviours. Support for these ideas is provided using data from junior doctors and their supervisors in a hospital emergency department. Adaptive role behaviours positively influenced supervisors’ judgements of overall job performance. This relationship was stronger for employees with high self-efficacy for achieving outcomes. Engaging in proactive role behaviours while also lacking role-breadth self-efficacy resulted in supervisors’ giving employees less credit for their proactive role behaviours. Findings support the argument that employees’ self-efficacy for specific role behaviours provides attributional cues about capability that modify how adaptive and proactive role behaviours are interpreted and valued.